Missed Injuries in Polytrauma Patients after Trauma Tertiary Survey in Trauma Intensive Care Unit. (December 2016) - Tammelin, E.; Handolin, L.; Söderlund, T.
Background and Aims: Injuries are often missed during the primary and secondary surveys in trauma patients. Studies have suggested that a formal tertiary survey protocol lowers the number of missed injuries. Our aim was to determine the number, severity, and consequences of injuries missed by a non-formalized trauma tertiary survey, but detected within 3 months from the date of injury in trauma patients admitted to a trauma intensive care unit. Material and Methods: We conducted a cohort study of trauma patients admitted to a trauma intensive care unit between 1 January and 17 October 2013. We reviewed the electronic medical records of patients admitted to the trauma intensive care unit in order to register any missed injuries, their delay, and possible consequences. We classified injuries into four types: Type 0, injury detected prior to trauma tertiary survey; Type I, injury detected by trauma tertiary survey; Type II, injury missed by trauma tertiary survey but detected prior to discharge; and Type III, injury missed by trauma tertiary survey and detected after discharge. Results: During the study period, we identified a total of 841 injuries in 115 patients. Of these injuries, 93% were Type 0 injuries, 3.9% were Type I injuries, 2.6% were Type II injuries, and 0, 1% were Type III injuries. Although most of the missed injuries in trauma tertiary survey (Type II) were fractures (50%), only 2 of the 22 Type II injuries required surgical intervention. Type II injuries presumably did not cause extended length of stay in the intensive care unit or in hospital and/or morbidity. Conclusion: In conclusion, the missed injury rate in trauma patients admitted to trauma intensive care unit after trauma tertiary survey was very low in our system without formal trauma tertiary survey protocol. These missed injuries did not lead to prolonged hospital or trauma intensive care unit stay and did not contribute to mortality. Most of the missed injuries received non-surgical treatment.